Research Findings On The Optimization Of Parameters For Working Tools In Combined Units - Naurizbaev A.O; Sadikov R.O (Genius Journals, 2024)
The article presents the design scheme and working tools of a combined unit and the results of theoretical studies to substantiate the main parameters of the working tools, as well as the arrangement scheme of the working tools for minimal processing of the upper ridge layer.
Keywords: combined unit; ridge processing; flat disk